Effect of Pathological Narcissism on Development of Early Maladaptive Schemas in Men Seeking Alcohol Use Disorders Treatment - Irem Anli; Yesim Can; Cuneyt Evren (Psikiyatride Güncel Yaklaşımlar, 2017)
We hypothesized that pathological narcissism of alcoholic individuals cause cognitive maladaptive schemas that lead to alcohol use disorders. We assessed the charts of 206 male patients with a diagnosis of alcohol use disorders according to DSM-5 that represent all male patients admitted into Bakirkoy Mental Health and Neurological Diseases Education and Research Hospital Alcohol and Drug Research, Treatment and Training Center (AMATEM) during this period. The control group consisted of 102 male participants without any problems related to alcohol use or any other psychiatric diagnosis Data collection tools were Young Schema Qustionnaire and ndash;Short Form, Self Psychology Inventory and Sociodemographic Data Form. According to our results there is a statistically significant difference between alcohol use disorders and normal group in terms of pathological narcissism and early maladaptive schemas.. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2017; 9(1.000): 63-74]